Ganglionic Acetylcholine Receptor Autoantibody: Oncological, Neurological, and Serological Accompaniments - McKeon, Andrew; Lennon, Vanda A; Lachance, Daniel H; Fealey, Robert D; Pittock, Sean J (Archives of neurology (Chicago), 2009)
OBJECTIVE To describe the clinical utility of the nicotinic ganglionic acetylcholine receptor (α3-AChR) autoantibody as a marker of neurological autoimmunity and cancer. DESIGN Case-control study. SETTING Mayo Clinic, Rochester, Minnesota. PATIENTS A total of 15 000 patients seen at Mayo Clinic (2005-2007) and evaluated on a service basis for paraneoplastic neurological autoimmunity for whom clinical information was obtained retrospectively by medical record review as well as 457 neurologically asymptomatic patients or control subjects of whom 173 were healthy, 245 had lung cancer, and 39 had systemic lupus erythematosus or Sjögren syndrome. OUTCOME MEASURES Neurological, oncological, and serological associations of α3-AChR autoantibody seropositivity. RESULTS Of 15 000 patients tested on a service basis, 1% were seropositive (median, 0.12 nmol/L; range, 0.03-18.8 nmol/L; normal, ≤0.02 nmol/L), 55% were male, and the median age was 65 years. Cancer was found (new or by history) in 24 of 78 patients evaluated for cancer while at Mayo Clinic (30%); 43% had adenocarcinoma (more patients had breast cancer than prostate, lung, and gastrointestinal cancers; each of the latter groups had about the same number of patients). Of 12 patients with high antibody values (≥1.00 nmol/L), 83% had pandysautonomia. Of 85 patients with medium antibody values (0.10-0.99 nmol/L), neurological presentations were more diverse and included peripheral neuropathies (36%), dysautonomia (20%, usually limited), and encephalopathy (13%). Of 58 patients with low antibody values (0.03-0.09 nmol/L), 54% had a nonautoimmune neurological disorder or no neurological disorder. Of 245 control patients with lung cancer, 7.8% were seropositive. Only 1 of 212 control patients without cancer (0.5%) was seropositive (P < .001). CONCLUSION The detection of α3-AChR autoantibody aids the diagnosis of neurological autoimmunity and cancer. Arch Neurol. 2009;66(6):735-741-->